EcologicalNetworks.jl: analysing ecological networks of species interactions. Issue 11 (17th October 2019) - Poisot, Timothée; Bélisle, Zachary; Hoebeke, Laura; Stock, Michiel; Szefer, Piotr
Abstract : Networks are a convenient way to represent many interactions among ecological entities. The analysis of ecological networks is challenging for two reasons. First, there is a plethora of measures that can be applied (and some of them measure the same property). Second, the implementation of these measures is sometimes difficult. We present 'EcologicalNetworks.jl', a package for the 'Julia' programming language. Using a layered system of types to represent several types of ecological networks, this packages offers a solid library of basic functions which can be chained together to perform the most common analyses of ecological networks.